Knockdown of liver-derived factor XII by GalNAc-siRNA ALN-F12 prevents thrombosis in mice without impacting hemostatic function. Issue 196 (December 2020) - Liu, Jingxuan; Cooley, Brian C.; Akinc, Akin; Butler, James; Borodovsky, Anna
Abstract: Background: Plasma coagulation Factor XII (FXII) plays a crucial role in contact activation, ultimately regulating both the kinin-kallikrein system and the intrinsic pathway of coagulation. A growing body of evidence suggests that inhibition of FXII can prevent thrombosis. Given FXII does not appear to modulate hemostasis, targeting FXII is a promising strategy for the prevention of pathological thrombus formation without the hemostatic risks typically associated with anticoagulants. To this end, a subcutaneously administered investigational RNAi therapeutic targeting liver F12 mRNA (ALN-F12) was developed. Aim: To investigate the thrombo-protective and hemostatic effects of FXII reduction by ALN-F12 in rodent thrombosis and hemostasis models. Methods: A single dose of ALN-F12 was subcutaneously administered to C57Bl/6 mice. After reaching steady state FXII reduction, the impact on thrombosis (ferric chloride arterial thrombosis and electrolytic injury induced venous thrombosis models) and hemostasis (saphenous vein injury and tail tip transection bleeding models) was evaluated. Result: Administration of ALN-F12 resulted in dose-dependent reductions of both liver F12 mRNA and plasma FXII protein. In mice, ALN-F12 led to dose-dependent reductions in platelet and fibrin accumulation in the venous electrolytic-injury model and in the time to occlusion in the ferric chloride arterial thrombosis model. At 10 mg/kg ALN-F12, the top dose level evaluated, this resulted in >95% reduction of FXII and ~10 fold reduction in fibrin deposition. Finally, hemostasis models showed that >95% reduction of FXII had no impact on bleeding time or blood loss. Conclusion: Our findings support that reduction of plasma Factor XII by ALN-F12 provided thrombo-protective effects with no increased bleeding risk in rodent models of thrombosis and hemostasis. Highlights: Plasma coagulation factor FXII is a potential target for thromboprophylaxis. GalNAc-siRNA ALN-F12 knocks down liver F12 and reduces plasma FXII levels. ALN-F12 treatment prevents thrombosis in mouse models. F12 knock down by ALN-F12 does not impact hemostasis in mice.